Effect of high temperatures on sandstone: a computed tomography scan study - Lintao, Yang; Marshall, Alec M.; Wanatowski, Dariusz; Stace, Rod; Ekneligoda, Thushan (Thomas Telford, 2017)
The impact of high temperatures on rocks is a topic of growing importance in geotechnical engineering due to its relevance to applications such as underground nuclear fuel storage, geothermal energy resource exploration and underground coal gasification. This paper presents results from tests performed on samples of sandstone treated to a range of temperatures between 20 and 1000°C. Sandstone samples obtained from underground coal gasification trial sites in Poland were selected for the tests. Multistage triaxial tests were used to determine the mechanical properties of the samples. X-ray diffraction and thermal analyses were performed to investigate the changes in physical and chemical properties of the samples under increasing temperature. Micro-computed tomography analyses were carried out on selected samples in order to show the microstructural changes that take place as a result of the heating process. Three-dimensional characterisation of sample porosity and pore-size distribution was performed to obtain a quantitative comparison between samples subjected to different temperature treatments. The relationship between microstructure and macro-mechanical characteristics of sandstone at high temperatures is discussed. The results illustrate that the mechanical properties of sandstone are closely related to alterations of microstructure that result from increased temperatures.